2013
DOI: 10.1161/strokeaha.112.675033
|View full text |Cite
|
Sign up to set email alerts
|

Self-Report of Stroke, Transient Ischemic Attack, or Stroke Symptoms and Risk of Future Stroke in the Reasons for Geographic And Racial Differences in Stroke (REGARDS) Study

Abstract: Background and Purpose History of stroke and Transient Ischemic Attack (TIA) are documented risk factors for subsequent stroke and all-cause mortality. Recent reports suggest increased risk among those reporting stroke symptoms absent stroke or TIA. However, the relative magnitude of increased stroke risk has not been described across the symptomatic spectrum: 1) asymptomatic (Asx), 2) stroke symptoms only (SS), 3) TIA, 4) stroke in the distant past (DS), and 5) recent stroke (RS). Methods Between 2003–2007 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 44 publications
(48 citation statements)
references
References 27 publications
3
42
0
3
Order By: Relevance
“…Most notably, while we reviewed medical records on suspected stroke events occurring during follow-up, we had to rely on self-reported stroke events occurring before participants were enrolled in study. However, these self-reported strokes at baseline have previously been found to be a reliable predictor of recurrent events, 18 a relationship confirmed herein. Perhaps more important, the specificity of self-reported stroke has been generally reported to be above 95% (and the sensitivity is generally above 80%), [19][20][21][22][23] suggesting that few individuals falsely self-reported stroke.…”
Section: Resultssupporting
confidence: 82%
“…Most notably, while we reviewed medical records on suspected stroke events occurring during follow-up, we had to rely on self-reported stroke events occurring before participants were enrolled in study. However, these self-reported strokes at baseline have previously been found to be a reliable predictor of recurrent events, 18 a relationship confirmed herein. Perhaps more important, the specificity of self-reported stroke has been generally reported to be above 95% (and the sensitivity is generally above 80%), [19][20][21][22][23] suggesting that few individuals falsely self-reported stroke.…”
Section: Resultssupporting
confidence: 82%
“…The differences between developed and undeveloped countries are related, probably, to the management of risk factors such as hypertension, diabetes, and smoking 20,21 . Liu et al 15 revealed a decrease of 21.4% in the incidence of stroke in 4 years in China between 1992 and 1995.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the authors intended to recruit 50% blacks in their study but could include only 38.6% blacks. 1 The authors did not discuss the reasons of lower recruitment of blacks in their study. Understanding the reasons for a lower recruitment rate is important to improve the recruitment of this community in the future stroke trials.…”
Section: To the Editormentioning
confidence: 94%
“…We read with great interest the recent article published by Judd et al 1 in which a study on risk of future stroke recurrence was described. The authors specifically studied different types of baseline ischemic strokes influencing US patients' future risk of ischemic stroke in a sample from the south eastern sector of the United States, also known as the stroke belt.…”
Section: To the Editormentioning
confidence: 99%
See 1 more Smart Citation